Topics on chaotic systems : selected papers from CHAOS 2008 International Conference, Chania, Crete, Greece, 3-6 June 2008 - Skiadas, Christos H.; Dimotikalis, Ioannis; Skiadas, Charilaos (World Scientific, 2009)
This volume includes the best papers presented at the CHAOS 2008 International Conference on Chaotic Modeling, Simulation and Applications. It provides a valuable collection of new ideas, methods, and techniques in the field of nonlinear dynamics, chaos, fractals and their applications in general science and in engineering sciences. It touches on many fields such as chaos, dynamical systems, nonlinear systems, fractals and chaotic attractors. It also covers mechanics, hydrofluid dynamics, chaos in meteorology and cosmology, Hamiltonian and quantum chaos, chaos in biology and genetics, chaotic.